Analisis Pengembangan Ekspor Pala, Lawang, dan Kapulaga Indonesia - Nurhayati, Ely; Hartoyo, Sri; Mulatsih, Sri (UI Scholars Hub, 2019)
Export is an important component in the economy. The higher export performance, the greater positive impact. From 2012 to 2016, Indonesia’s exports continued to decline, so Indonesia needs to boost its exports. One of the potential commodities to be developed is nutmeg, mace, and cardamoms. This study analyzed the competitiveness of nutmeg, mace, and cardamoms, as well as the factors affecting its exports. The methods used are RCA, EPD, X-Model, and Gravity. The competitiveness analysis showed that the optimistic export markets were Pakistan, Germany, Italy, and USA. The potential export markets were Malaysia, Vietnam, Thailand, France, and Netherlands. Factors that affecting exports were GDP per capita, price, economic distance, and tariff.